MXene Titanium Carbide-based Biosensor: Strong Dependence of Exfoliation Method on Performance - Chia, Hui Ling; Mayorga-Martinez, Carmen C; Antonatos, Nikolas; Sofer, Zdeněk; Gonzalez-Julian, Jesus J; Webster, Richard D; Pumera, Martin (Analytical chemistry, 2020)
Transition metal carbides, known as MXenes, are generated via the selective etching of "A" layers from their layered, ternary parent compounds, MAX phases, where M corresponds to early d-transition metal, A being a main group sp-element from either Group 13 or 14 and carbon or nitrogen being denoted by X. MXenes are being recognized as a new and uprising class of 2D materials with extraordinary physical and electrochemical properties. The huge specific surface area and outstanding electrical conductivity of MXenes, make them ideal candidates for sensing and energy applications. Herein, we demonstrated the successful incorporation of pristine MXene, Ti3C2 produced via HF etching and subsequent delamination with TBAOH, as a transducer platform toward the development of a second generation electrochemical glucose biosensor. Chronoamperometric studies demonstrate that the proposed biosensing system exhibits high selectivity and excellent electrocatalytic activity toward the detection of glucose, spanning over wide linear ranges of 50-27 750 μM and possess a low limit of detection of 23.0 μM. The findings reported in this study conceptually proves the probable applications of pristine MXenes toward the field of biosensors and pave ways for the future developments of highly selective and sensitive electrochemical biosensors for biomedical and food sampling applications.
Keywords: glukosa; elektrochemické techniky; biosenzitivní techniky; Biosensing Techniques; titan; Glucose; Titanium; Electrochemical Techniques